ҚЫЗЫЛ ИЕК ЭПИТЕЛИЙІНІҢ ҰЙЫМДАСУ ҚҰРЫЛЫМЫНА ƏРТҮРЛІ ДОЗАДАҒЫ ХЛОРЛЫ КАДМИЙДІҢ ƏСЕР КӨРСЕТУ ЕРЕКШЕЛІКТЕРІ (Experimental biology, 2015)
Chronic exposure to cadmium chloride leads to a significant violation of the structural integrity of the gum tissue, an increase of intercellular space and decrease the bulk density desmosomalnyh contacts, expansion ofinterstitium, reducing the intensity of the blood-tissue exchange, which causes inhibition of transport of lymph from the gums.
Keywords: cadmium chloride leads